THE USE OF FILM AS MULTIMODAL MEDIA TO FACILITATE STUDENTS’ MULTIMODAL LITERACY IN LEARNING NARRATIVE TEXTS - Rendi Afriadi (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2026)
ABSTRACT This study aimed to investigate the effectiveness of using films as multimodal media in facilitating students’ multimodal literacy in narrative text learning. The study was motivated by the need for more interactive and contextual EFL learning media. A pre-experimental design with a one-group pre-test and post-test was employed involving 26 tenth-grade vocational high school students. Data were collected through pre-tests, post-tests, and questionnaires, then analyzed using paired sample t-tests and descriptive statistics. The findings revealed an improvement in students’ mean scores from 86.15 to 90.30 after the implementation of film-based learning. The paired sample t-test showed a statistically significant difference (t(25) = -14.774, p < 0.05), indicating that films were effective as multimodal media in narrative text learning. Questionnaire results also demonstrated positive student responses with an overall mean score of 4.10, particularly in terms of text comprehension, learning motivation, engagement, and multimodal literacy. The findings indicate that the integration of films supports language comprehension while strengthening students’ ability to interpret meaning through multiple modes of communication. In conclusion, the use of films as multimodal media effectively enhances students’ narrative text comprehension and multimodal literacy. This study highlights the importance of innovative multimodal media in creating more meaningful EFL learning experiences. ABSTRAK Penelitian ini bertujuan menyelidiki efektivitas penggunaan film sebagai media multimodal dalam memfasilitasi literasi multimodal siswa pada pembelajaran teks naratif. Penelitian ini dilatarbelakangi oleh kebutuhan media pembelajaran EFL yang lebih interaktif dan kontekstual. Penelitian menggunakan desain pra-eksperimen dengan rancangan one-group pre-test dan post-test terhadap 26 siswa kelas X SMK. Data dikumpulkan melalui pre-test, post-test, dan angket, kemudian dianalisis menggunakan paired sample t-test dan statistik deskriptif. Hasil penelitian menunjukkan adanya peningkatan nilai rata-rata siswa dari 86,15 menjadi 90,30 setelah penerapan pembelajaran berbasis film. Uji paired sample t-test menunjukkan perbedaan yang signifikan (t(25) = -14,774, p < 0,05), yang menandakan bahwa film efektif sebagai media multimodal dalam pembelajaran teks naratif. Hasil angket juga menunjukkan respons positif siswa dengan rata-rata skor 4,10, terutama pada aspek pemahaman teks, motivasi belajar, keterlibatan, dan literasi multimodal. Temuan ini menunjukkan bahwa integrasi film mampu mendukung pemahaman bahasa sekaligus memperkuat kemampuan siswa dalam menginterpretasikan makna melalui berbagai mode komunikasi. Kesimpulannya, penggunaan film sebagai media multimodal efektif dalam meningkatkan pemahaman teks naratif dan literasi multimodal siswa. Penelitian ini menegaskan pentingnya penggunaan media multimodal inovatif dalam menciptakan pembelajaran EFL yang lebih bermakna.